Two New Clustering Algorithms for Vehicular Ad-Hoc Network Based on Ant Colony System - Fathian, Mohammad; Shiran, Gholam Reza; Jafarian-Moghaddam, Ahmad Reza (Wireless personal communications, 2015)
In vehicular ad-hoc network (VANET), vehicles are dynamic nodes communicating with each other by wireless technology in their own transmission range. Consequently, with regard to larger communication due to the greater number of vehicles and high mobility of nodes, communication management and creation of a stable network in VANET are most challenging subjects. Hence, clustering as a possible solution to address this challenge, should take into consideration to produce stable clustering structure. Clustering technique is for organizing nodes into groups, making the network more robust and scalable. This paper introduces two new Improved Ant System-based Clustering algorithm (IASC1 and IASC2) suitable for dynamic environment of the VANET. Simulation is run to evaluate the introduced methods and compare them with the most commonly VANET clustering algorithms as found in the literature review. Results reveal the proposed algorithms have improved the stability and the runtime of VANET clustering algorithm and have a relatively good performance compared with other algorithms.